Politics of Law for the Protection of Debtors as Consumers in Fintech based Loaning Services - Dinda Dinanti; Muthia Sakti; Indira Putri Irfani; Sinta Ana Pramita (Universitas Negeri Semarang, 2020)
This study aims to analyze legal protection related to technology-based lending and borrowing services. The research method used is normative legal research, with a statutory approach, namely an approach using legislation and regulations, and a conceptual approach that refers to existing legal doctrines. The data collection technique used was a literature study. The results show that legal protection for debtors as consumers has not been realized because the consumer dispute resolution mechanism for non-PUJK activities has not been regulated, there is no regulation regarding the interest rate ceiling and mechanisms related to the collection process, and because of the lack of strict sanctions against online loan administrators who commit violations.